Two species of Agaricus sect. Xanthodermatei from Thailand - Rui-Lin Zhao; Dennis E. Desjardin; Philippe Callac; Luis A. Parra; Jacques Guinberteau; Kasem Soytong; Samantha Karunarathna; Ying Zhang; Kevin D. Hyde (My University, 2013)
Agaricus murinocephalus is described and illustrated as a new species. This taxon, presently known only from Thailand, is characterized by a context that generally does not discolor on exposure, the lack of a phenolic odor, a cap covered by very fine, appressed, dark grey squamules outside the grey disc on a whitish background, and a broken collar-like annulus. Agaricus endoxanthus , previously reported from South America, Europe, and Asia, is recorded for the first time in Thailand. Morphological and published molecular analyses place both taxa in A . sect. Xanthodermatei based on.
Keywords: Sect; Fungal Biology and Applications